Marine debris from the past - Contamination of the Brazilian shore by a WWII wreck. (July 2021) - Teixeira, Carlos Eduardo Peres; Cavalcante, Rivelino Martins; Soares, Marcelo Oliveira; Ribeiro, Felipe Bezerra; Bezerra, Luis Ernesto Arruda
Abstract: In 2018, unidentified packages appeared along approximately 1600 Km of the Brazilian coastline causing widespread pollution to beaches and danger to society. The packages were found to be bales of raw rubber ranging in size from 0.06 m³ to 3.4 m³ and weighing up to 200 kg. A few bales were marked with the stamp "Product of French Indochina" and colonized by the barnacle Lepas anatifera, an oceanic species. We found that unidentified packages are from a Second World War (WWII) shipwreck, and that the source is almost certainly the SS Rio Grande found at 5, 762 m depth. Numerical simulations show that currents can carry out the bales from the SS Rio Grande to the beaches. We highlight transnational measures to study and protect the WWI shipwrecks because they represent an overlooked environmental risk. Highlights: Unidentified packages were found along 1600 km of the Brazilian coastline in 2018 and 2019. They are identified as crude natural rubber in bales from French Indochina (<1943). These rubber bales are probably coming from a German ship sunk during the WWII (1944). We also hypothesized that this marine debris come from the deepest shipwreck (~5.800m depth) on the world's oceans. Mapping and management of deep ocean shipwrecks need to be embraced since they represent a source of marine pollution.